Pertanggungjawaban Hukum Terhadap Tindakan Agen Diplomatik Dari Negara Pengirim Yang Melakukan Spionase Di Negara Penerima - Ahmad Sandy Dewana; Akbar Kurnia Putra (Fakultas Hukum Universitas Mulawarman, 2021)
Abuse of authority by diplomatic officials from member countries of the 1961 Vienna Convention for personal gain or certain groups is still common. This situation is undoubtedly contrary to their duties and functions as representatives of their country. The formulation of the problem raised is how to form a legal settlement based on the 1961 Vienna Convention and the Optional Protocol concerning the Requirement to Settle Disputes. The research method used is a normative juridical type with a Legislative, Conceptual, and Case approach. The primary legal materials used are the Vienna Convention On Diplomatic Relations April 18, 1961, and the Optional Protocol Concerning the Compulsory Settlement Of Disputes Of Vienna Convention On Diplomatic Relations; Meanwhile, the secondary legal materials used are books, research journals, research reports, various scientific works, articles and various other sources that can support primary legal materials; Tertiary legal materials consist of dictionaries, internet, and so on that can support primary and secondary legal materials. The results of this study indicate that apart from Persona non-Grata, there are other ways to impose sanctions on diplomatic agents who abuse their authority, in this case, espionage activities. Keywords: Diplomatic Agent; Espionage; Sending State